P253 Isoniazid and Multi-Drug Resistant Mycobacterium Tuberculosis: The East London Experience. (12th November 2015) - Liddicoat, H; Mohd-Afzal, S; Potter, J; White, V; Jayasekera, N; Darmalingam, M; Kunst, H
Abstract : Introduction: East London has one of the UK's largest cohorts of Drug Resistant Tuberculosis (DR-TB). This paper aims to provide insight into the recent behaviour of DR-TB in a multi-ethnic urban TB clinic. Methods: A retrospective study was conducted on all patients with DR-TB between 2007 and 2013. Statistical analysis was performed using Fisher's Exact Test. Results: 179 cases were identified: 126 patients had Isoniazid mono-resistance (H-Mono), 3 had poly-resistance including Isoniazid, and 37 patients had multi-drug resistant TB (MDR-TB). There were 6 cases of Rifampicin mono-resistance, 1 Ethambutol mono-resistance, and 6 Pyrazinamide mono-resistance. H-Mono and MDR-TB were more prevalent in males (58% and 57% respectively). H-Mono predominated in younger age groups (mode age group 25–29) whilst MDR-TB had a more uniform age distribution (Figure 1 ). The ethnicities of patients with DR-TB reflected the local population (Indian Subcontinent: 57% of H-Mono and 52% MDR-TB; Africa: 16% for both; Caucasian: 11% and 16% respectively; Other: 16% for both). The majority were non-UK born, however a meaningful proportion were UK-born (H-Mono 17% and MDR-TB 14%). Patients from all WHO world regions with DR-TB were more likely to have H-Mono, apart from Eastern Europe, where MDR-TB was more common (p = 0.005). The proportion of patients with pulmonary TB was similar in both cohorts (54% H-Mono and 65% MDR-TB, p = 0.26), as was the proportion of patients who were sputum smear-positive (46% and 38% respectively, p = 0.64). More patients with MDR-TB had a history of previous TB diagnosis compared to patients with H-Mono (p = 0.0005). Of note, the 5 UK-born patients with MDR-TB were all under the age of 40 with no specific risk factors or previous TB treatment. The number of TB notifications fell during this period, however the proportion of patients with MDR-TB remained stable at approximately 1%. In contrast, cases with any drug resistance reduced. Conclusion: H-mono and MDR-TB shared many demographical features, but in this cohort there were significant differences in age distribution, previous diagnosis of TB and country of origin. A significant proportion of patients did not match the typical profile of DR-TB, highlighting the importance of culture to exclude drug-resistance in all individuals.